Fellowship as the Foundation of Corrupt Leadership in Nigeria - Odia, Sylvester Idemudia; Osawuru, Osamede Christopher (NIU Journal of Humanities, 2023)
Corrupt leadership has a great influence on followership. However, it is generally believed by many Nigerians including Chinua Achebe that the problem with Nigeria is squarely the problem of leadership. The argument present to substantiate the above claim is that countries in other parts of the world that have advanced economically and politically did so on the basis of good leaders. The role played by the citizens of such countries as followers is often ignored. Nigeria, like any other country, is peopled by stakeholders who are both leaders and followers. It then behooves on every Nigerian to rise to the occasion of saving and securing Nigeria as we are all major stakeholders as Nigerians. The success or otherwise of leadership will not be in isolation of followership. Both leaders and followers are guilty in the event of the failure of the State. The support given to leaders in Nigeria, always allowing them to have their way in almost everything is a sign of poor followership. Using the critical and analytic methods, this paper observed that politics that have succeeded all over the world are those that enjoy vibrant, active and participatory followership, and argued that the kind of followership in Nigeria where by the followers swallow the pills administered to them by their leaders even when such pills are bitter, cannot lead Nigeria to oneness, economic and political greatness. The paper concludes that the guilt in the collapse of project Nigeria is to be shared between the leadership and the followership, and recommends active participation by all citizenry in the project Nigeria with more powers exercised by the followership in protecting their interest. Keywords: Nigeria Project, Citizenry, Followership, Leadership, Social Contract, Politics.